The expression of hepatoma upregulated protein in human endometrium during the menstrual cycle - Takahashi, Akimasa; Yamanaka, Akiyoshi; Takebayashi, Akie; Kimura, Fuminori; Murakami, Takashi (Gynecological Endocrinology, 2021)
Human endometrium resists embryo implantation except during the window period. Currently, uterine HURP expression is known to be involved in endometrial stromal proliferation during embryo implantation of mice. Thus, we demonstrated hepatoma up-regulated protein (HURP) expression in the human endometrium during the menstrual cycle, as well as HURP regulation in endometrial stromal cells (ESCs). We collected human endometrial samples from different menstrual cycle phases (early/late proliferative, and early/mid/late secretory), and then analyzed these samples by immunohistochemistry, reverse transcription-polymerase chain reaction, and Western blotting. We also assessed the effects of two sex-steroid hormones, 17β-estradiol (E2) and 4-pregnene-3,20-dione (P4) on the cultured stromal cells. HURP protein was localized to the nucleus of the endometrial both epithelial and stromal cells in all stages. Also, HURP mRNA and protein in human endometrial tissue was significantly up-regulated during late-proliferative and secretory phase, compared with early-proliferative phase. In ESCs, HURP expression was regulated by E2, but not P4. We indicated that cyclic changes in HURP expression in human normal ESC strongly suggested up-regulation by estrogen. Taken together, since estrogen responses are fundamental in endometrial biology, uterine expression of HURP may be involved in female reproductive function during the menstrual cycle.